Central serous chorioretinopathy secondary to childbirth. (6th December 2010) - Hirji, Nashila; Watt, Lynda; Richardson, Emma
Abstract : A previously healthy 37-year-old woman presented with decreased vision in the right eye, noted suddenly during childbirth. Fundus examination revealed elevation at the right macula, and optical coherence tomography confirmed central serous chorioretinopathy in the right eye. No intervention was undertaken, and the symptoms and clinical findings resolved spontaneously over 2 months.